PENGARUH SEDIMENTASI DAN TURBIDITY PADA JEJARING MAKANAN EKOSISTEM AIR MENGALIR (LOTIK) - Tjokrokusumo, Sabaruddin Wagiman (Jurnal Hidrosfir Indonesia, 2008)
Sedimentation and turbidity are contributed significantly to decrerasing population of biotic organisms in aquatic ecosystem. Impact to faunal population in lotic environment may be expressed by pervasive change in local food chains starting from primary trophic levels. Decreasing in primary production associated with increasing a number of sediment content dan high in turbidity value and impact on negative level of production of food availability related to a number of zooplankton, insects, freshwater molusca, and then fish. Direct effect of each trophic levels is affected to mortality levels, decreasing physiologicsl function, and rejection, however decreasing food availability at the trophic level that resulted in depressing growthrate, reproduction and recruitment function. The effect of turbidity on aquaticorganisms often as inconsistent in watershed and water treatment. But in this case the different is significantly because of lack of correlation between sediment concentration (mg/liter) and measurement unit (NTU). The use of NTU as a unit measurement in change with suspended sediment (TSS) to predict the effect of aquatic biota in watershed is ambigious. At the same time, NTU measurement in different watershed is depending on the concentration of suspended sediment. To monitore the effect of turbidity in local watershed we are recommended to use the baseline data to investigate the effect of local watershed that arecorrelated betweensuspended sediment and NTU This study could be happenned through a series of monitoring of water flow based on seasonal dynamic and then by using this baseline data, we are creating a useful solution to decrease sediment input into the river water.